Comparison of early enteral nutrition in severe acute pancreatitis with prebiotic fiber supplementation versus standard enteral solution: A prospective randomized double-blind study - Karakan, Tarkan (Baishideng Publishing Group Co., Limited, 2007)
AIM: To compare the beneficial effects of early enteral nutrition (EN) with prebiotic fiber supplementation in patients with severe acute pancreatitis (AP). METHODS: Thirty consecutive patients with severe AP, who required stoppage of oral feeding for 48 h, were randomly assigned to nasojejunal EN with or without prebiotics. APACHE II score, Balthazar’s CT score and CRP were assessed daily during the study period. RESULTS: The median duration of hospital stay was shorter in the study group [10 ± 4 (8-14) d vs 15 ± 6 (7-26) d] (P < 0.05). The median value of days in intensive care unit was also similar in both groups [6 ± 2 (5-8) d vs 6 ± 2 (5-7) d]. The median duration of EN was 8 ± 4 (6-12) d vs 10 ± 4 (6-13) d in the study and control groups, respectively (P > 0.05). Deaths occurred in 6 patients (20%), 2 in the study group and 4 in the control group. The mean duration of APACHE II normalization (APACHE II score < 8) was shorter in the study group than in the control group (4 ± 2 d vs 6.5 ± 3 d, P < 0.05). The mean duration of CRP normalization was also shorter in the study group than in the control group (7 ± 2 d vs 10 ± 3 d, P < 0.05). CONCLUSION: Nasojejunal EN with prebiotic fiber supplementation in severe AP improves hospital stay, duration nutrition therapy, acute phase response and overall complications compared to standard EN therapy.